Secondary Metabolites and Potential Antioxidants of Nutmeg (Myristica fragrans Houtt) Mace from West Java - Rahmatul Kartini Erza; Karmanah Karmanah; Nurlela Nurlela (JURNAL SAINS NATURAL, 2022)
Nutmeg mace is a mesh-shaped seed coat that is bright red when the fruit is ripe and yellowish-white when immature, which generally contains secondary metabolites such as flavonoids and phenolics. This study aimed to examine the content of flavonoids and phenolics, the antioxidant activity of ethanol extract of the nutmeg (Myristica fragrans Houtt) mace based on three regions in West Java i.e. Sukabumi, Cianjur, and Bogor District with age differences. Total phenolic content was measured spectrophotometrically using the Folin Ciocalteau reagent. The total flavonoid content was quantitatively measured using the AlCl3 colorimetric method. Antioxidant activity was tested by measuring the IC50 using the 2,2-diphenyl-1-picryl hydrazyl (DPPH) method. The highest phenolic content was found in young nutmeg from Sukabumi Regency (76.40 mgTAE/g). The highest flavonoid content was found in old age mace nutmeg from Bogor Regency (20.33 mgQE/g). Nutmeg mace has the potential as a natural antioxidant because it can reduce free radicals in DPPH with the lowest IC50 of 153.5 mg/L in old mace from Cianjur District.Keywords: Myristica fragrans Houtt; Mace; Phenolic; Flavonoid; Antioxidant ActivityABSTRAKKandungan Metabolit Sekunder Dan Potensi Antioksidan Fuli Buah Pala (Myristica Fragrans Houtt) Dari Jawa BaratFuli pala adalah selubung biji berbentuk jala berwarna merah terang ketika buah sudah matang dan berwarna putih kekuningan ketika belum matang, yang  umumnya mengandung senyawa metabolit sekunder diantaranya flavonoid dan fenolik. Tujuan penelitian ini  untuk menguji kandungan senyawa flavonoid, fenolik dan aktivitas antioksidan ekstrak etanol fuli pala (Myristica fragrans Houtt) berdasarkan tiga wilayah yaitu Kabupaten Sukabumi, Kabupaten Cianjur dan Kabupaten Bogor dengan perbedaan usia. Kadar total fenolik diukur spektrofotometri menggunakan reagen Folin Ciocalteau, Kadar total flavonoid secara kuantitatif dengan metode kolorimetri AlCl3. Aktivitas antioksidan diuji dengan mengukur nilai IC50 dengan metode 2,2- difenil-1-pikril hidrazil (DPPH). Kadar fenolik tertinggi didapatkan pada pala usia muda dari Kabupaten Sukabumi dengan kadar sebesar 76,40 mgTAE/g. Kadar flavonoid tertinggi didapat pada fuli pala usia tua di Kabupaten Bogor dengan kadar sebesar 20,33 mgQE/g. Fuli buah pala berpotensi sebagai antioksidan alami karena mampu meredam radikal bebas pada DPPH dengan IC50 terendah sebesar 153,5 mg/L yang diperoleh dari fuli usia tua dari Kabupaten Cianjur.Kata kunci: Myristica fragrans Houtt; Fuli; Fenolik; Flavonoid; Aktivitas Antioksidan